2018
DOI: 10.1164/rccm.201710-2079oc
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Vascular Remodeling and Right Heart Failure in Pulmonary Arterial Hypertension with a HIF-2α Inhibitor

Abstract: These findings demonstrate that pharmacological inhibition of HIF-2α is a promising novel therapeutic strategy for the treatment of severe vascular remodeling and right heart failure in patients with PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 51 publications
6
130
0
Order By: Relevance
“…The critical role of HIF2 in the development of hypoxia-induced PH has raised significant interest in targeting HIF2 for treatment of PH patients. In fact, one study has already demonstrated a quite effective role of a HIF2 inhibitor in reversing PH in animal models (40). However, small animal models for PH have well-recognized limitations (41).…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of HIF2 in the development of hypoxia-induced PH has raised significant interest in targeting HIF2 for treatment of PH patients. In fact, one study has already demonstrated a quite effective role of a HIF2 inhibitor in reversing PH in animal models (40). However, small animal models for PH have well-recognized limitations (41).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that target the inhibition of HIF transcription in PH patients could be an interesting new perspective in the treatment of hypertension. For example, it has been demonstrated that HIF-2 inhibited by C76 is capable of relieving pulmonary artery blood pressure in different models ( Dai et al, 2018 ).…”
Section: Hypoxia-inducible Factors and Potential Therapeutic Targetsmentioning
confidence: 99%
“…Although increased HIF2α protein stability has been identified in pulmonary vascular occlusive lesions from both IPAH patients and rodent PH models, the mechanistic role of Recent studies by Dai et al [39] and Hu and colleagues [40] offers further support for the important role of HIF2α in PH and confirmed many of these inflammatory and signalling target genes. Furthermore, Hu et al utilised PT2567 in a hypobaric hypoxic rat model of PH and reported a reduction in both pulmonary arterial pressures and vascular remodelling [40].…”
Section: Discussionmentioning
confidence: 96%